Intertwined institutionalization: pressures on Vietnam's accounting profession during transition to IFRS. Issue 4 (20th August 2020) - Nguyen, Lan Anh; Vesty, Gillian; Kend, Michael; Nguyen, Quan; O'Connell, Brendan
Abstract : Purpose: The purpose of this paper is to understand the institutionally driven changes impacting organizational accounting manipulation in Vietnam's emerging transitional economy. Specifically, this study explore how Vietnamese accountants and regulators explain questionable accounting transactions and their rationalization for those practices, especially during the period of accounting system transition from Vietnamese accounting standards to International Financial Reporting Standards (IFRS). Design/methodology/approach: The study uses interview-based methods involving 22 Vietnamese accountants, financial managers, audit partners and regulators. Findings: This study have found dysfunctional approaches to revenue and expense recognition underpinned by institutional theory. At play is a combination of opportunities relating to weak accounting standards and organizational controls; management pressure; and a desire to avoid unwanted scrutiny from Vietnamese regulators. Research limitations/implications: This study does not include the views of non-financial managers or other accounting users. Future research could focus more on the perceptions of these other stakeholder groups. Practical implications: Accounting manipulation can be collusive, therefore, regulators should have a stricter view and broader examination in the monitoring process. Originality/value: This study examine accounting manipulation through the lens of New Institutional Sociology and also share the views of the accountants and regulators. This study argue that weak accounting standards are not the only factors contributing to accounting manipulation. When evaluating the existence of accounting manipulation, this paper find a combination of factors including: opportunities for manipulation, pressure from management and the rationale behind the conduct. These factors should be interpreted in context.